(untitled) (Scientific journal of the Fergana State University, 2024)
There was no homogenous change in enzyme activity in the soils scattered around the oil field and oil storage facility, including urease enzyme 2.25 times, phosphatase enzyme activity 1.76 times, and dehydrogenase enzyme 0.42 times more damage and reduced activity in the soils around the oil field. Catalase enzyme activity decreased by 1.3 times and invertase enzyme activity decreased by 1.22 times in light gray soils around the oil storage facility.